Investigation of the prevalence of Head Lice and Factors Affecting Them in Infected People Referring to Gerash County Health Center - Elham Rezaee; Fatemeh Heidari; Mohammad Nowrouzi (Shahrekord University of Medical Sciences, 2020)
Background and aims: Pediculosis is one of the most common parasitic diseases that affect a wide range of age groups. The prevention of head lice infections promotes the physical and mental health of people in the community. Thus, the aim of this study was to investigate the prevalence of head lice infections and the factors affecting them in those who referred to health centers in Gerash County from 2011 to 2018. Methods: This descriptive cross-sectional study was conducted on patients suspected with head lice infections in health centers in Gerash. These infections were diagnosed by observing adult lice, nymphs, or nits on the head with the help of a magnifying glass. The collected data were then analyzed using SPSS software, version 22 and P˂ 0.05 was considered as the significance level. Results: In general, 66410 patients suspected with head lice were examined, of whom 2,547 cases (3.83%) were reported with confirmed infections including 2395 female (94.03%) and 152 male (5.97%) cases. The highest levels of infections were reported in the age group of 6-10 years while the lowest levels of infections were found in children less than 6 years of age. A significant statistical relationship was observed between head lice and gender, age, season, and the place of residence, and year of infection (P<0.05). Conclusion: Due to the increasing trend of head lice infections in recent years, pediculosis is still considered a health problem. Therefore, training on personal hygiene, adequate access to health services, and early diagnosis and treatment can play an important role in the prevention and elimination of head lice.